MANAGEMENT OF INSOMNIA IN AGING POPULATIONS: COMPARING THE INFLUENCE OF BENZODIAZEPINES AND Z-DRUGS ON COGNITIVE HEALTH AND NEURODEGENERATIVE RISK - A REVIEW OF THE LITERATURE - Piech, Bartosz; Dubaj, Magdalena; Judzińska , Alicja; Trojanowska, Emilia; Osipowska, Julia; Ignarska, Justyna; Sobczyńska, Kamila; Terbosh, Magda; Kwolek, Marlena; Kubicz Mzabi , Sabina (International Journal of Innovative Technologies in Social Science, 2026)
Background: Insomnia is a prevalent sleep disorder among older adults and is associated with impaired cognitive function and increased risk of neurodegenerative diseases. Pharmacological management commonly involves benzodiazepines and non-benzodiazepine “Z-drugs” (zolpidem, zaleplon, zopiclone), which act as sedative-hypnotics through modulation of GABAA receptors. Although cognitive-behavioral therapy is the first-line treatment, hypnotic medications remain widely prescribed.Aim: This review evaluates the mechanisms linking benzodiazepines and Z-drugs to neurodegeneration and summarizes the clinical and epidemiological evidence regarding their long-term impact on cognitive function in older adults.Methods: A literature review was conducted using PubMed, PMC, and Google Scholar databases, focusing on full-text, English-language publications from 2013–2025. Search terms included “benzodiazepines and dementia risk,” “Z-drugs and cognitive impairment,” and drug-specific names such as zolpidem, zopiclone, zaleplon, and diazepam. Both observational and mechanistic studies were considered.Results: Long-term benzodiazepine use is consistently associated with an increased risk of cognitive decline and dementia, particularly with higher cumulative doses and long-acting compounds. Evidence for Z-drugs suggests a generally more favorable cognitive profile at low doses or short-term use, although high-dose or long-term exposure may similarly increase dementia risk and adverse events such as falls and fractures. The underlying mechanisms involve modulation of GABAergic neurotransmission, potentially altering hippocampal and cortical network activity, synaptic plasticity and memory consolidation. The interpretation of causality is complicated by potential confounding factors, such as underlying insomnia or anxiety.Conclusion: Benzodiazepines and Z-drugs are effective for insomnia management in older adults but may carry long-term cognitive risks. Minimizing dose, limiting treatment duration, and prioritizing non-pharmacological interventions such as cognitive-behavioral therapy are essential strategies to mitigate potential neurodegenerative outcomes. Future studies should aim to optimize dose–response regimens, incorporate long-term follow-up assessments, clarify the biological mechanisms through which these drugs affect cognitive function and include randomized controlled trials as well as long-term observational studies to more precisely evaluate the effects on specific cognitive domains, such as memory, attention and executive function.